Towards a Sustainable Future: Evaluating Sovereign Sukuk in Indonesia, the UAE, and Morocco - Khairunnisa Musari; Abdelbari El-Khamlichi (International Journal of Islamic Khazanah, 2025)
As contemporary instruments of Islamic finance, sovereign sukuk play a pivotal role in driving economic growth while advancing sustainable development. The sovereign sukuk initiative has opened new pathways for financing infrastructure, promoting social welfare, supporting environmental stewardship, and fostering impact investment aligned with the Sustainable Development Goals (SDGs). This study examines the utilization of sovereign sukuk as sustainable financing mechanisms in three leading Muslim-majority countries, namely Indonesia, the United Arab Emirates (UAE), and Morocco. Indonesia pioneered its first sovereign sukuk in 2008 and, a decade later, became the world’s first issuer of a green sovereign sukuk, signaling its leadership in Islamic sustainable finance. The UAE, which launched its inaugural sovereign sukuk in 2014, has recently expanded into the green sukuk market through several landmark issuances, despite being a relatively new participant in this segment. In contrast, Morocco—having entered its first decade of sukuk implementation—issued its debut sovereign sukuk in 2018 and plans to release its second in 2025, reflecting a more gradual trajectory. Drawing upon literature review and content analysis, this study provides a comparative exploration of the sovereign sukuk experiences of these three nations. It focuses on: (1) The experience of Indonesian sovereign sukuk; (2) The experience of the UAE sovereign sukuk; (3) The experience of the Moroccan sovereign sukuk; (4) Comparative analysis of the initial development, law, and regulations of the sovereign sukuk in financing or refinancing eligible green projects that contribute positively to environmental sustainability. The findings highlight how sovereign sukuk can serve as effective instruments for sustainable financing, bridging Islamic ethical principles with global environmental and social objectives.